2017
DOI: 10.1016/j.jcrimjus.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of victim-perpetrator relationship, reputation and initial point of resistance on officers' responsibility and authenticity ratings towards hypothetical rape cases

Abstract: The impact of victim-perpetrator relationship, reputation, and initial point of resistance on officers' responsibility and authenticity ratings towards hypothetical rape cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 96 publications
(165 reference statements)
4
39
3
Order By: Relevance
“…Specialist training was also a significant contributor to the explained variance in RMA. This supports some previous work demonstrating lower RMA in specially trained officers (see Lee et al, 2012), but challenges other studies which highlight no significant differences between those who have received specialist training and those who have not (Goodman-Delahunty & Graham, 2011;Sleath & Bull, 2012), and work which actually demonstrates a negative effect of specialist training on judgements of perpetrator responsibility (in acquaintance cases, where the victim resists late; Hine & Murphy, 2017). Findings for officer age also challenge existing research (e.g.…”
Section: Demographic Predictorssupporting
confidence: 81%
See 2 more Smart Citations
“…Specialist training was also a significant contributor to the explained variance in RMA. This supports some previous work demonstrating lower RMA in specially trained officers (see Lee et al, 2012), but challenges other studies which highlight no significant differences between those who have received specialist training and those who have not (Goodman-Delahunty & Graham, 2011;Sleath & Bull, 2012), and work which actually demonstrates a negative effect of specialist training on judgements of perpetrator responsibility (in acquaintance cases, where the victim resists late; Hine & Murphy, 2017). Findings for officer age also challenge existing research (e.g.…”
Section: Demographic Predictorssupporting
confidence: 81%
“…Subsequently, when such expectations are violated, there is an associated impact on levels of belief, victim blame, and perpetrator exoneration, as well perceived authenticity of the claim, as officers evaluate reports of rape against their predetermined ideas of what rape should look like (Hazelwood & Burgess, 1995). Indeed, extra-legal factors are often present in officers' definitions of rape cases (Campbell & Johnson, 1997;Hazelwood & Burgess, 1995;Mennicke et al, 2014), and several studies have demonstrated that when rapemyth associated information is present, officers are likely to make negative judgements regarding victim and perpetrator responsibility, as well as rape authenticity (Goodman-Delahunty & Graham, 2011;Hine & Murphy, 2017;Lee, Lee, & Lee, 2012;Schuller & Stewart, 2000;Sleath & Bull, 2012;Venema, 2016b). Such research supports the potential influence of individual attitudinal variability on officers' judgements and decision-making in rape cases (Edwards, Turchik, Dardis, Reynolds, & Gidycz, 2011;Kelly, 2010).…”
Section: Rape Myths and Investigative Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst several studies have sought to substantiate claims that jurors construct competing narratives during trial and others have examined the importance of particular story features in isolation including plausibility, coherence, and completeness upon an assessors determination of credibility and guilt (Campbell, Menaker, & King, 2015;Canter, Grieve, Nicol, & Benneworth, 2003;Hine & Murphy, 2017;Jackson, 1996;Voss & Van Dyke, 2001;Yale, 2013), no researchers to date have developed and validated a complete scale which permits comprehensive testing of such an assertion. With existing juror bias scales adequately testing the importance of legal attitudes upon verdict decisions (Kassin & Wrightsman, 1983;Lecci & Myers, 2008;Lundrigan, Dhami, & Mueller Johnson, 2016), the need for an empirical test of the decision making process itself remained apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations are particularly important considering the vital role played by officers as gatekeepers to the criminal justice system (Sleath & Bull, 2015). Thus far, studies have principally assessed the manifestation of rape myths within officer populations in three ways: first, by examining levels of rape myth acceptance (RMA) in officers (see Sleath & Bull, 2017, for review); second, by identifying the presence of rape myths in officers' definitions and/or classifications of rape (e.g., Mennicke et al, 2014); and third, by examining the influence of rape myth-related information on officers' judgements (of, for example, victim credibility, e.g., Page 2007Page , 2008aPage , 2008bPage , 2010or victim responsibility, e.g., Hine & Murphy, 2017). Few studies have however, at present, directly explored the relationship between officers' rape myth acceptance and their judgements of the crime and those involved.…”
Section: Introductionmentioning
confidence: 99%